Peculiar features of the supracomplexes formation in the Keivy domain - Kozlov, N. Е.; Sorokhtin, N. О.; Martynov, E. V.; Marchuk, T. S. (2021)
The Keivy domain (the northeastern part of the Arctic zone of the Fennoscandian Shield) during the period of the maximum manifestation of the Late Archean collisional processes was overlapped by tectonic allochthons of adjacent microcontinents thrust over it, submerged relative to other blocks of the continental crust, and acquired the features of a classical middle massif. In the process of studies that allow a detailed description of the formation of the supracrustal complexes of the Keivy structure, it has been found that the formation processes of the Kola orogeny had a pronounced spatial and temporal zoning and impulsive character. The maximum degree of orogeny was experienced by the rock associations of the Murmansk domain, as a result of which terrigenous material transported from its mountain slopes prevailed in the metasedimentary complexes of the Keivy domain throughout the entire period of their formation. The substance removed from the Murmansk domain was more actively accumulated in the metasedimentary rocks of the Lebyazhinsky suite; then a regular attenuation was observed within all domains, but at the last stage of the formation of the section of the Keivy sedimentary strata, the structural-material complexes of the Murmansk domain again begin to degrade more actively. A detailed study of the compositional features of the supracrustal complexes of the Keivy structure refutes the currently emerging point of view on the coeval formation of alkaline granites and felsic metavolcanics of the Lebyazhinsky suite. It can be argued with a high degree of probability that the rocks used to draw this conclusion (for which the age of 2.678 ± 7 Ma) is not typical of the supracrustal section of the metavolcanics of the Lebyazhinsky suite and are metasomatites. Кейвский домен (северо-восточная часть Арктической зоны Фенноскандинавского щита) в период максимального проявления позднеархейских коллизионных процессов был перекрыт надвинутыми на него тектоническими аллохтонами сопредельных микроконтинентов, ...